REAKSI LIKENOID ORAL DIHUBUNGKAN DENGAN HIPERSENSITIVITAS TERHADAP TUMPATAN AMALGAM (Studi Pustaka) - Yohana Gowara; Titiek Setyawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Until recently the etiology and pathogenesis of oral lichenoid reaction remain unclear. Usually lichenoid reaction is associated with systemic disease or particular drugs such as ACE inhibitor anti hypertension and several dental materials. Amalagam restorations have been reported as the most frequent cause of oral lichenoid reaction induced by dental materials. Mercury hypersensitivity is predicted to be responsible in inducing the reaction. The aim of this review was to describe oral lichenoid reaction associated with hypersensitivity to dental amalgam, so the clinician can manage the cases properly. In conclusion, replacement the amalgam filling which contact to the oral mucosa with other inert dental materials would be useful for hypersensitive patient.